Implementing Inclusive Education in Lithuania: What are the main Challenges according to Teachers’ Experiences? - Lakkala, Suvi; Juškevičienė, Agnė; Česnavičienė, Jūratė; Poteliūnienė, Sniegina; Ustilaitė, Stasė; Uusiautti, Satu (Acta Paedagogica Vilnensia, 2019)
The purpose of this article was to analyse the challenges primary and subject teachers had experienced concerning the implementation of inclusive education in Lithuanian primary schools, progymnasiums and gymnasiums. In this study, 86 Lithuanian teachers reflected on their experiences of teaching in heterogeneous classes. The data were collected from 13 group interviews. The article highlights the challenges encountered by the primary and subject teachers in implementing inclusive teaching. The findings were arranged under four themes. Concerning teachers’ pedagogical competence, the teachers highlighted difficulties in differentiating their teaching and including the students with special educational needs in the classes’ social peer networks. Teachers also pointed out the need for multiprofessional collaboration and dialogue with parents. The themes were then interpreted in the theoretical frames of teachers’ professional competences. At a practical level, the study’s findings may help teacher educators understand the teacher competences needed to implement inclusive education and support them to develop existing teaching programs to target the successful implementation of inclusive education. At a conceptual level, this study presents evidence for preparing teachers to work in the conditions of striving towards inclusive education.